The Effects of Interval Feedback on The Self-Efficacy of Netball Umpires - Mahoney, Alison J. (Asist Group, 2008)
The present study used quantitative and qualitative methods to explore the relationship between interval feedback and self-efficacy toward umpiring netball games. Grade “A ”level umpires (n = 7) provided feedback to umpires (n = 40) under two conditions; 1) interval feedback given at the end of one tournament game (after 14 minutes) and again at the end of a second consecutive game (after 28 minutes), and 2) feedback at the end of the game (after 28 minutes). Umpires in both conditions completed an Umpiring Self-Efficacy Questionnaire (USEQ) which was a 14-item measure designed to assess factors relevant to netball umpire performance. Participants completed the USEQ immediately before game one, during the interval, and after a second game. Umpires also completed a feedback questionnaire which enabled them to reflect on the feedback received. A repeated measures factorial (time x feedback condition) ANOVA indicated no significant interaction effect (F = 0.05, p > .05), and no main effect for condition (F = 0.06, p > .05) or time (F = 1.61, p > .05) for changes in self-efficacy. Although there were no significant effects, qualitative data alluded to aspects of feedback perceived to enhance umpire self-efficacy, thus identifying ways in which feedback might have a more consistent effect. Practical implications of the study in relation to verbal interval feedback are discussed.